2021
DOI: 10.1177/00222437211037340
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Expressions and Brand Status

Abstract: This project investigates emotionality by brands on social media. First, we analyze a field dataset of over 200,000 text and images posts by brands across two major platforms. Using recent automated text analysis (Study 1a) and computer vision methods (Studies 1b and 1c), we provide initial documentation of a negative relationship between brand emotionality and status. Exploring this relationship further, in Studies 2, 3, and 4, we find that brands can leverage this association, reducing emotionality in brand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 90 publications
0
15
0
Order By: Relevance
“…(2018), who agree on the descriptive and engaging power of visual contents. Also, the study has revealed how group communication has a positive effect (H2) on the attention of the stakeholders due to the authority and the greater soundness that can be achieved by involving the brand and the referencing group (Lee, 2021). Subsequently, the study does not verify the third hypothesis and highlights how the disclosure of innovation-related topics has a positive impact on favorites and retweets number but assumes an adverse effect on the comments.…”
Section: Discussionmentioning
confidence: 99%
“…(2018), who agree on the descriptive and engaging power of visual contents. Also, the study has revealed how group communication has a positive effect (H2) on the attention of the stakeholders due to the authority and the greater soundness that can be achieved by involving the brand and the referencing group (Lee, 2021). Subsequently, the study does not verify the third hypothesis and highlights how the disclosure of innovation-related topics has a positive impact on favorites and retweets number but assumes an adverse effect on the comments.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 44.3 % of UK-based internet users were active on Twitter in January 2021 ( Kemp, 2021 ). Thus, in line with prior brand-related social media research (e.g., Borah et al, 2020 , Golmohammadi et al, 2021 , Lee, 2021 , Rust et al, 2021 ), Twitter was used as a data source for this study ( Boegershausen et al, 2022 ). Approximately 327,205 tweets were extracted that matched the search criteria (described in detail below) using the social listening tool Pulsar TRAC ( https://www.pulsarplatform.com ).…”
Section: Methodsmentioning
confidence: 99%
“…We show that the persuasive effects of facial emojis are not restricted to consumer-consumer interactions but also occur when brands use facial emojis in social media interactions and digital advertising. Thus, we contribute to the recent literature (Lee, 2021) by showing that brands can use similar language, specifically facial emojis, to communicate persuasively with consumers in online interactions.…”
Section: Introductionmentioning
confidence: 91%